(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
Bacterial wilt of tobacco caused by Ralstonia solanacearum poses a significant threat to tobacco cultivation in Bangladesh. In this study, fourteen tobacco growing areas of Bangladesh were surveyed to assess the status of bacterial wilt disease in tobacco. The result revealed that the higher level of bacterial wilt incidence and severity was recorded in Bandarban followed by Naikhonchari, Lama, Rangpur, and Lalmonirhat and the lower level was in Chakaria, Kushtia, Meherpur, Chuadanga, and Jhenaidah. However, a moderate level of incidence and severity was recorded in Manikgonj, Khagrachori, and Tangail. After estimating the bacterial population in the soil of respective regions it was observed that the highest bacterial population was counted at 22.4 x 107 CFU/g soil in Chakaria and the lowest was counted at 4.3 x 107 CFU/g soil in Tangail. Among the seed samples, sample no BWT Seed 21 had the highest level of infection (93%), sample no BWT Seed 37 had a medium level (39.46%), and sample no BWT Seed 57 had the lowest level of infection (5.14%) with R. solanacearum as detected by plating tobacco seed samples by TTC agar medium. Biovar and races of R. solanacearum were identified through the sugar oxidation test and pathogenicity test and it was found that R. solanacearum isolates from all the fourteen growing areas were grouped into race 1 and biovar 1, biovar 2, biovar 3. Genetic diversity of R. solanacearum analysis was done by using REP and ERIC primers where both primers showed three clusters (I, II, and III) at 60% similarity. The results are very crucial for the development of sustainable management of bacterial wilt of tobacco and for future population analyses of R. solanacearum. Asian Australas. J. Biosci. Biotechnol. 2023, 8(3), 56-69